Bahasa Inggris - Christiani, Maria Riche; Adhariani, Desi (E-Jurnal Akuntansi, 2025)
A strong risk culture plays an important role in the effectiveness of risk management in public sector organizations. The evaluation of risk culture at Service Office X, a unit under Ministry Y, applies the risk culture model from The Institute of Risk Management (IRM) (2012a) and the coercive isomorphism mechanism in Institutional Theory (1983). A qualitative approach with an evaluation case study method, utilizing primary data from surveys and interviews as well as secondary data from organizational documents. Findings indicate a Mercenary organizational culture with high solidarity but low social interaction. The RCA Model assessment confirms that Risk Leadership and Risk Resources are well-established, while Responding to Bad News, Accountability, Transparency, Risk Decisions, and Rewarding Appropriate Risk Taking need improvement. Institutional Theory suggests that risk culture formation aligns with the coercive isomorphism mechanism. Keywords: Risk Culture, Risk Management, Public Sector, IRM, Institutional Theory